2022
DOI: 10.1002/smll.202202917
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Facet Engineering of MXene‐Derived TiN Nanoflakes as Efficient Bidirectional Electrocatalyst for Advanced Lithium‐Sulfur Batteries

Abstract: The design of nanomaterials with grain orientation structure by crystal facet engineering is of great significance for boosting the catalytic ability and electrochemical properties, but the controllable synthesis is still a challenge. Here, TiN nanoflakes with exposed (001) facets are prepared using 2D Ti3C2 MXene as the initial reactant and applied as a bidirectional electrocatalyst for the reduction and oxidation process in lithium‐sulfur batteries (LSBs). The (001) facet‐dominated TiN nanoflakes have a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In particular, TiN nanoflakes with exposed (001) facets derived from Ti 3 C 2 MXene catalyzed both the discharge and charge processes in Li-S batteries to facilitate the conversion of soluble lithium polysulfides to Li 2 S 2 /Li 2 S and decomposition of Li 2 S, respectively. 383 Another MXene analogue of Mo 5 N 6 as cathode material was reported to boost the performance of Na-S batteries (Fig. 20g).…”
Section: Sulfur Conversion Reactionsmentioning
confidence: 99%
“…In particular, TiN nanoflakes with exposed (001) facets derived from Ti 3 C 2 MXene catalyzed both the discharge and charge processes in Li-S batteries to facilitate the conversion of soluble lithium polysulfides to Li 2 S 2 /Li 2 S and decomposition of Li 2 S, respectively. 383 Another MXene analogue of Mo 5 N 6 as cathode material was reported to boost the performance of Na-S batteries (Fig. 20g).…”
Section: Sulfur Conversion Reactionsmentioning
confidence: 99%
“…Since then, numerous nanostructured nitrides as sulfur cathodes are well developed, resulting in significant improvements in cycle performance. Over more recent times, titanium nitrides (TiN) hold great interest to be implemented as sulfur anchoring sites which deliver a much stable cycling span 150–153 . Zhang group proposes a multifunctional titanium nitride separator to retard polysulfides dissolution, fabricated by a simple coating process (Figure 10A).…”
Section: Metal Nitridesmentioning
confidence: 99%
“… 27 Peng et al prepare MXene-derived TiN nanoflakes as sulfur host and study the catalytic action, which demonstrate that the (001) facet-dominated TiN nanoflakes have a strong adsorption capacity for LiPSs. 28 Nevertheless, only a few studies about TiN with hollow structure applied as sulfur hosts have been reported due to the limited preparation strategies and technologies. Therefore, the design of MXene/TiN composite materials with more edge sites can accelerate electron/ion transport, improve the catalytic effect of the material on LiPSs, and further improve the utilization rate of the active substance sulfur.…”
Section: Introductionmentioning
confidence: 99%